Bridging the Pedagogical Gap Between Operational and Contextual Affordances with Social Media - Wilson Otchie; Emanuele Bardone; Margus Pedaste (University of Bologna, 2022)
The usage of social media in education is increasing as a result of perceived pedagogical benefits. The literature emphasizes the importance of teachers continuing to build their social media capabilities, experiences, and values. Critical thinking, problem-solving, and the ability to contextualize social media require intellectual, social, and ethical talents regardless of operational proficiency. We performed a semi-structured interview with 13 high school teachers who expressed their thoughts and experiences using social media in the classroom. The interviews' recorded videos were transcribed into text and coded inductively and deductively for analysis. The study's findings agreed with a proposed conceptual framework that claims that regular interactions with social media enable teachers to better understand and teach with it. The paper presents a framework to assist education facilitators, educational technologists, teachers, and other affiliated agencies in refocusing their efforts on technology-assisted context training. It also emphasizes the significance of engaging with technology regularly.